1989
DOI: 10.1007/bf00272113
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced cerebral lesions in childhood

Abstract: Post-irradiation cerebral pathologies may appear in various forms from localized radiation necrosis to a plurifocal type or from local to diffuse vasculopathies. Contrary to the current prevalent opinion, these lesions are not rare in children since young nerve tissue is particularly sensitive to ionizing radiation. Given the seriousness of some of these lesions, the authors recommend careful evaluation of the risk involved in relation to the real necessity of administering irradiation therapy in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…29 This finding is supported by several previous studies of CNS tumors, 2,5,19,21,[30][31][32] as well as of other secondary malignant neoplasms (SMNs). 13 It has been reported that radiation at a young age leads to the development of meningioma within a shorter time.…”
Section: Discussionsupporting
confidence: 88%
“…29 This finding is supported by several previous studies of CNS tumors, 2,5,19,21,[30][31][32] as well as of other secondary malignant neoplasms (SMNs). 13 It has been reported that radiation at a young age leads to the development of meningioma within a shorter time.…”
Section: Discussionsupporting
confidence: 88%
“…This may be because more chromosomal injury is caused by radiation in the developing nervous tissue of young children 7 and the meninges of children are extremely sensitive and, thus, more vulnerable to radiation. 27 Thirdly, the relationship between the dose of radiation and the latency period is still uncertain: some authors have demonstrated a proportional relationship between a high dose of irradiation (> 20 Gy), particularly in children, and the risk of induced meningiomas with a shorter latency period. 2,5,8,28 however others have not shown a significant correlation between latency period and radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…How radiotherapy increases the risk of development of meningioma is not completely understood, but it is known that arachnoid cells in childhood are very sensitive to radiation,17 and given that meningiomas arise from the cap cells of the arachnoid, cellular damage at this level induced by irradiation may not be unconnected with the development of meningiomas. It has also been shown that radiation induces hydroxyl-free radicals that cause strand breaks or base damage in DNA.…”
Section: Discussionmentioning
confidence: 99%